ANALISIS KEPASTIAN HUKUM PENERAPAN DIVERSI DALAM PUTUSAN PENGADILAN NEGERI BANJARNEGARA NOMOR 4/PID.SUS-ANAK/2019/PN.BNR - Mischaela Ivane Maureen Marbun; R Rahaditya (Jurnal Hukum Adigama, 2021)
Children are the next generation of the nation's struggle ideals. The position of the Child as a young generation needs to have the opportunity to grow and develop reasonably both spiritually, physically, and socially. The purpose of child legal protection is to ensure the fulfillment of children's rights, to live, grow, develop and participate optimally, and get protection from violence and discrimination, in one of them is a diversion. The diversion itself according to Law No. 11 of 2012 on The Child Criminal Justice System Article 1 paragraph (7) is the transfer of the settlement of the Child's case from the criminal justice process to the process outside the criminal justice. The issues raised concerning the legal certainty of the application of diversion in the decision of the Court No. 4/Pid.sus-anak/2019/PN.Bnr stipulated in Law No. 11 of 2012. The purpose of this research is to provide an overview related to the implementation and application of diversion in criminal acts committed by children in case studies of court decisions No. 4 / Pid.sus-anak / 2019 / PN.Bnr. The research methods used are normative, descriptive research specifications. The secondary Legal materials obtained are analyzed in perspective with a legal and case approach. The results of the analysis obtained in the form of an overview of legal certainty diversion in the case of the child, which still must protect the rights of the child, because every decision taken affects the future of the child.